The correlation of anxiety and depression with C3 and C4 Levels and systemic lupus erythematosus activity - Hamzah Shatri; Purnamandala; Rudy Hidayat; Robert Sinto; Alvina Widhani; Rudi Putranto; Rr Dyah Purnamasari; Eka Ginanjar; Chyntia Olivia Maurine Jasirwan (BMC Psychiatry, 2023)
Abstract Background Anxiety and depression are psychosomatic disorders that are frequently observed in chronic conditions such as systemic lupus erythematosus (SLE). Anxiety and depression can be induced by immunological and neurotransmitter dysregulation, which is characterized by hypothalamic–pituitary–adrenal (HPA) axis dysfunction, production of proinflammatory cytokines, and activation of complement in the blood, such as C3 and C4. The causes of anxiety and depression in SLE are complex, ranging from neuropsychiatric involvement to drug adverse effects. Detecting anxiety and depression symptoms in SLE patients is critical to preventing disability from impacting quality of life. Objective To assess the relationship between anxiety and depression symptomatology, SLE disease activity with levels of C3 and C4 in Cipto Mangunkusumo National Hospital. Methods This study used a cross-sectional design. The study included 120 SLE patients from Cipto Mangunkusumo National Hospital, aged 18 to 60 years. All patients were requested to complete a Hospital Anxiety and Depression Scale (HADS) questionnaire to assess their anxiety and depression symptoms. Subjects with anxiety and depression were assessed for disease activity using the Mexican Systemic Lupus Erythematosus Systemic Disease Activity (Mex-SLEDAI), and blood samples were collected to test complement C3 and C4 levels. Spearman's correlation test was used to examine the relationship between HADS scores, Mex-SLEDAI, and C3 and C4 levels. Results The results of the study showed a very weak statistically significant negative correlation between anxiety symptoms based on HADS and C3 levels (r = -0.189; p = 0.038) and a weak correlation between anxiety symptoms and C4 levels (r = -204; p = 0.026). Depressive symptoms based on HADS revealed a very poor connection and no statistical significance with levels of C3 (r = -0.056; p = 0.546) and C4 (r = -0.068; p = 0.461). Anxiety (r = 0.06; p = 0.173) and depression (r = 0.031; p = 0.753) symptoms have a weak and insignificant positive connection with SLE activity. Conclusion C3 and C4 serum levels appeared to decrease when the presence of anxious symptoms increased. There was no significant correlation in SLE disease activity between anxious and depressed patients.